PENTINGNYA MEMAHAMI KITAB WAHYU DALAM KEHIDUPAN JEMAAT - Toding, Yulianus (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2023)
The book of Revelation is a book that is classified as difficult to interpret because it contains various symbols that are not easy to understand, to be able to understand and understand the purpose of this letter, this article is written with a literary approach to describe a number of things including methods and ways of interpreting the book of Revelation so that the meaning contained in it is easy to capture and understand. Based on the results of the author's research, the book of Revelation has a number of benefits for the church today, especially in the midst of situations and conditions that are faced with a number of challenges and problems, the book of Revelation is present to provide strength and comfort as well as provide firmness of faith to the congregation that God in Jesus Christ has power that cannot be defeated by any power so that faith in Jesus will enable us to go through every difficulty of life and will enjoy the crown of life later with God in Heaven.